Juridical Aspects Of Complementary Traditional Medicine In Indonesia - Siswanto, Bambang; Setiawati, Sri; Sumantri Riyanto, Ontran (CV. Inara, 2022)
Alternative, complementary medicine is non-conventional medicine aimed at improving public health status, including promotive, curative, preventive, and rehabilitative efforts obtained through structured education with high quality, safety, and effectiveness based on biomedical science, which has not been accepted in conventional medicine. In several hospitals in Indonesia, this complementary medicine has begun to be applied as supportive therapy or replacement therapy for patients who refuse traditional treatment methods. This complementary therapy can also be carried out at the patient's request or with the referral of other doctors. The approach method used in this study, namely normative juridical, is a method of legal research conducted on library materials or secondary data using deductive thinking methods based on truth criteria. Coherent. There is also a complementary therapy called holistic medicine, which is because the form of therapy can affect individuals. The limitations of conventional medicine are one of the reasons why complementary and alternative therapies are an option in treating/healthy Indonesian people. The development of complementary and alternative therapies must be the responsibility of health workers, especially nurses. Legality for complementary and integrated health services must have a Traditional Health Worker Registration Certificate (STRTKT) and a Traditional Health Worker Practice License (SIPTKT).